The Preparation of Student Worksheets (LKPD) Based on Guided Inquiry on Straight Motion Material - Putri Zuhra; Elisa Elisa; A Halim (Asian Journal of Science Education, 2019)
This study aims to produce products namely guided inquiry-based LKPD on straight-motion material, knowing that LKPD is feasible to be used as a tool to help students learn, and knowing teacher and student responses to guided inquiry-based LKPD. This research uses the Research and Development (R D) method with the ADDIE model. The research subjects were 2 expert lecturers to validate guided inquiry-based LKPD, 17 SMP Negeri 3 Lhoknga students, and 2 Physics teachers. Data collection techniques were obtained from teacher interviews, LKP validation sheets, through student questionnaires, and teacher questionnaires. The data analysis technique uses descriptive qualitative. The results of data analysis showed that guided inquiry-based LKPD validation on straight-motion material "was feasible" in the systematic preparation. LKPD can be used by students as student learning aids. Student responses to guided inquiry-based LKPD obtained a percentage of 85% of students giving agreed responses to LKPD. And the teacher's response to this LKPD was 88%. Based on the results of the research conducted, guided inquiry-based LKPD can already be used in the learning process in the classroom.